Dynamics of avalanche-generated impulse waves: three-dimensional hydrodynamic simulations and sensitivity analysis - Chisolm, Rachel E. (2018)
Original abstract: This paper studies the lake dynamics for avalanche-triggered glacial lake outburst floods (GLOFs) in the Cordillera Blanca mountain range in Ancash, Peru. As new glacial lakes emerge and existing lakes continue to grow, they pose an increasing threat of GLOFs that can be catastrophic to the communities living downstream. In this work, the dynamics of displacement waves produced from avalanches are studied through three-dimensional hydrodynamic simulations of Lake Palcacocha, Peru, with an emphasis on the sensitivity of the lake model to input parameters and boundary conditions. This type of avalanche-generated wave is an important link in the GLOF process chain because there is a high potential for overtopping and erosion of the lake-damming moraine. The lake model was evaluated for sensitivity to turbulence model and grid resolution, and the uncertainty due to these model parameters is significantly less than that due to avalanche boundary condition characteristics. Wave generation from avalanche impact was simulated using two different boundary condition methods. Representation of an avalanche as water flowing into the lake generally resulted in higher peak flows and overtopping volumes than simulating the avalanche impact as mass–momentum inflow at the lake boundary. Three different scenarios of avalanche size were simulated for the current lake conditions, and all resulted in significant overtopping of the lake-damming moraine. Although the lake model introduces significant uncertainty, the avalanche portion of the GLOF process chain is likely to be the greatest source of uncertainty. To aid in evaluation of hazard mitigation alternatives, two scenarios of lake lowering were investigated. While large avalanches produced significant overtopping waves for all lake-lowering scenarios, simulations suggest that it may be possible to contain waves generated from smaller avalanches if the surface of the lake is lowered.